Physical and Psychological Symptom Biomechanics in Moderate to Advanced Heart Failure. Issue 4 (July 2015) - Denfeld, Quin E.; Mudd, James O.; Gelow, Jill M.; Chien, Christopher; Hiatt, Shirin O.; Lee, Christopher S.
Abstract : Background: There is a common dissociation between objective measures and patient symptomatology in heart failure (HF). Objective: The aim of this study was to explore the relationship between cardiac biomechanics and physical and psychological symptoms in adults with moderate to advanced HF. Methods: We performed a secondary analysis of data from 2 studies of symptoms among adults with HF. Stepwise regression modeling was performed to examine the influence of cardiac biomechanics (left ventricular internal diastolic diameter, right atrial pressure [RAP], and cardiac index) on symptoms. Results: The average age of the sample (n = 273) was 57 ± 16 years, 61% were men, and 61% had class III or IV HF. Left ventricular internal diastolic diameter ( β = 4.22 ± 1.63, P = .011), RAP ( β = 0.71 ± 0.28, P = .013), and cardiac index ( β = 7.11 ± 3.19, P = .028) were significantly associated with physical symptoms. Left ventricular internal diastolic diameter ( β = 0.10 ± 0.05, P = .038) and RAP ( β = 0.03 ± 0.01, P = .039) were significantly associated with anxiety. There were no significant biomechanical determinants of depression. Conclusion: Cardiac biomechanics were related to physical symptoms and anxiety, providing preliminary evidence of the biological underpinnings of symptomatology among adults with HF.